Electrochemical Analysis of Carbon-Based Supercapacitors Using Finite Element Modeling and Impedance Spectroscopy - Ahmad Azizpour; Niko Bagovic; Nikolaos Ploumis; Konstantinos Mylonas; Dorela Hoxha; Ferry Kienberger; Nawfal Al-Zubaidi-R-Smith; Georg Gramse (Energies)
The electrochemical performance of carbon-based supercapacitors containing ionic liquid electrolytes was investigated through calibrated impedance spectroscopy and finite element modeling (FEM). To ensure precisely calibrated complex impedance measurements over a wide frequency range the measured pouch cells were mounted in a pressure fixture with stable terminal contacts, and a two-term impedance calibration workflow was applied. For the physical interpretation of the measurement results, FEM was used. Experimental findings demonstrated a clear dependency of the capacitive behavior on the electrode material, where cells with activated carbon electrodes showed lower impedance compared to cells with graphene electrodes. For FEM, we used a volume-averaged approach to study the effect of the electrode structure on the EIS response of the cells. The simulated impedance results showed a good agreement with experimental data in the middle- to high-frequency regions, ranging from 10 Hz to 10 kHz. Deviations from the ideal Warburg impedance were observed at lower frequencies, suggesting nonlinearity effects of the porous structure on ion transport mechanisms. FEM analysis was performed for both graphene and activated carbon electrodes showing a steeper transition region for activated carbon electrodes, indicating a reduced diffusion resistance for electrolyte ions.